(untitled) (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
The procurement suite and external service management systems face a variety of integration problems, which means that they often create operational inefficiencies for organizations. In the article, Modulus Ticketing is explained as a brand new modular ticketing solution with a seamless integration into procurement suites and also solves problems associated with the current systems, such as the complex user setup requirements and ticketing history. There are numerous benefits attached to Modulus, including eliminating repetitive logins, the capability of linking workflows directly into Modulus, automated resolution of tickets during processing, and a significant increase in the amount of time saved per ticket resolved. The benefits of the Modulus Ticketing solution include the elimination of many of the shortcomings of previous (legacy) systems and a scalable solution that will continue to drive improvement in procurement support through a truly unified data approach and application of intelligent/automated data utilization. Other future ambitions in development, such as intake management modules, will support the modular ticketing concept. The article further states that there have been some updated words and phrases that have been revised to have a broader interpretation and can be applied to a larger audience while still remaining consistent with systems such as Ivalua and ServiceNow. The findings of this study suggest that all companies should modernize their procurement support systems and enhance their tools in order to realize the most efficiency and usability from these systems.